The Disabled Community Empowerment Model with Social Entrepreneurship Approach to Tenoon Business - Jasiyah, Rabiyatul; Suriadi (SEULANGA SYSTEM PUBLISHER, 2024)
The idea of community-oriented resource management (local resource management) is a development management figure that tries to answer development challenges like poverty, environmental degradation, and the lack of community participation in the development process that concerns them. This research aims to build an inclusive community empowerment model through a social entrepreneurship approach in the creative economy sector. This study uses a qualitative descriptive method which includes data collection through observation, interviews, and documentation using key and additional information. Data analysis techniques used are data collection, data reduction, data presentation and conclusion.The results of the study show that the model of empowering people with disabilities with a social entrepreneurship approach in tenoon businesses is based on the strengths and capabilities of people with disabilities so that through empowerment with a social entrepreneurship approach in the creative economy sector it can produce self-recognition, self-confidence and self-reliance that can support person, power and profit on strengthening the next empowerment.